Breast cancer risk factors and outcome a global perspective - Nirmala Bhoo Pathy ([Utrecht University], 2011)
Breast cancer results in significant mortality and morbidity across the globe. In asia, the burden of breast cancer is increasing at an alarming rate.However, there seems to be a paucity of studies to answers important questions pertaining to breast cancer in Asian settings.